Attracting Consumer Food: The Effect of Perceived Crowdedness - Amru Bangkit Adhitama; Kurniawati Kurniawati; Yolanda Masnita (Journal of Social Research, 2023)
This study delves into the interplay between Perceived Crowding (Crowd) and its impact as a mediator on Purchase Intention, Customer Satisfaction (SAT), and Word of Mouth (WoM). Specifically, it examines the role of crowd perception as a deciding factor for selecting a restaurant, thereby influencing overall consumer satisfaction. The research comprises a sample of 100 respondents, spanning multiple generations. The data analysis technique employed is Structural Equation Modeling (SEM). The findings of this study underscore the significant mediating role played by Perceived Crowding (Crowd) on the relationship between Purchase Intention and both Customer Satisfaction (SAT) and Word of Mouth (WoM). This insight suggests that the presence of crowds acts as a crucial factor in shaping customers' purchase decisions, overall satisfaction, and likelihood to engage in positive word-of-mouth referrals. Interestingly, the research highlights the distinct behavior of the millennial generation and Generation Z. These younger demographics exhibit a penchant for aligning with current trends. Even when faced with long queues at a food establishment, they display a willingness to wait, suggesting a correlation between crowd perception, purchase intent, and consumer behavior in these generational groups. This study underscores the importance of understanding the dynamics of Perceived Crowding and its role in influencing consumer behavior, particularly among the younger generations. It sheds light on the complex interrelationships between Purchase Intention, Customer Satisfaction, and Word of Mouth, offering valuable insights for businesses in the food industry seeking to optimize customer experiences and harness the power of positive word-of-mouth promotion.